2020
DOI: 10.3390/toxins12090555
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fungi and Multi-Class Mycotoxins in Camelia sinensis and Herbal Teas and Dietary Exposure Assessment

Abstract: In this paper, a study of fungal and multi-mycotoxin contamination in 140 Camellia sinensis and 26 herbal teas marketed in Latvia is discussed. The analysis was performed using two-dimensional liquid chromatography with time-of-flight mass spectrometry (2D-LC-TOF-MS) and MALDI-TOF-MS. In total, 87% of the tea samples tested positive for 32 fungal species belonging to 17 genera, with the total enumeration of moulds ranging between 1.00 × 101 and 9.00 × 104 CFU g−1. Moreover, 42% of the teas (n = 70) were contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 60 publications
0
17
1
Order By: Relevance
“…This preparatory step can have an enormous influence on the results as can be seen by the MS studies searching for mycotoxins in tea ( C. sinensis ). Reinholds et al (2020) found that in 140 different samples almost 97% of black teas, 88% of green teas and 100% of oolongs included in their study contained quantifiable levels of fungus with all Puerh (Chinese fermented tea) samples containing mycotoxins despite having the lowest levels of fungal contamination. Conversely, Monbaliu et al (2010) analysed 91 teas and found only one sample of Ceylon melange to be contaminated with no mycotoxins in the drinkable products despite also testing Puerh.…”
Section: Resultsmentioning
confidence: 96%
“…This preparatory step can have an enormous influence on the results as can be seen by the MS studies searching for mycotoxins in tea ( C. sinensis ). Reinholds et al (2020) found that in 140 different samples almost 97% of black teas, 88% of green teas and 100% of oolongs included in their study contained quantifiable levels of fungus with all Puerh (Chinese fermented tea) samples containing mycotoxins despite having the lowest levels of fungal contamination. Conversely, Monbaliu et al (2010) analysed 91 teas and found only one sample of Ceylon melange to be contaminated with no mycotoxins in the drinkable products despite also testing Puerh.…”
Section: Resultsmentioning
confidence: 96%
“…Extensive research in Lithuania shows that 45% of "teas" samples of various species shows the presence of deoxynivalenol at levels between 129 and 5,463 µg/kg. Moreover, six "teas" containing rose fruits (dog fruits), midland hawthorn fruits, St. John‘s Wort, purple coneflower, and herbal blend (mixture of birch, bearberry, knotgrass, rest harrow, parsley, nettle, yarrow, elderberry) contained deoxynivalenol over 2000 µg/kg (Reinholds et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…in spices, aroma (Fogele et al, 2018) and medicinal herbs (Chen et al, 2020). A recent survey carried out by Reinholds et al (2020) revealed an almost absolute prevalence of Aspergillus spp. in C. sinensis and herbal (camomile, peppermint, linden, hibiscus, rosehip fruits) teas, followed by Penicillium spp.…”
Section: Introductionmentioning
confidence: 99%
“…MLs vary from 5 to 30 µg/kg (Sedova et al, 2018). Besides aflatoxins and OTA, surveys report the detection of Fusarium (trichothecenes, zearalenone (ZEN), fumonisins (FBs), enniatins (ENNs)) and Alternaria toxins, cyclopiazonic and mycophenolic (MPA) acids, sterigmatocystin (STE), and citrinin (Bogdanova et al, 2020;Reinholds et al, 2019Reinholds et al, , 2020Rocha-Miranda and Venâncio, 2019;Santos et al, 2009;Sedova et al, 2018;Veprikova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%